KONSEP PERBUATAN CABUL DALAM KEBIJAKAN HUKUM PIDANA - Dhina Megayati (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
Obscene is an indecent desire or action that leads to sexual acts committed to achieve self-satisfaction outside the bond of marriage. As for the definition of obscene acts in general namely obscene acts is an act that is considered to violate the norms of decency (politeness) in the community environment, all of it within the scope of one's sexual lust. Crime of obscenity as one of the crimes classified as a crime against decency that violates human rights. The crime of obscenity is an act that by someone violates the norms of good religious norms, law, customs and decency that apply in society. This study aims to analyze and identify the concept of obscene acts in criminal law policy. This research is a normative research with a statue approach, conceptual approach, case approach, and futuristic approach. Based on the research done that this concept of what policy obscenity in criminal law where the formulation of punishment and sanctions for an offender listed in article: 289, 290, 292, 293, 294, 295, dan 296 KUHP all of them are crimes, whereas for victims listed in several statutory regulations namely Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection and Law Number 11 of 2012 concerning the Criminal Justice System for Children. In the future, it is necessary to have a policy in criminal law especially in the case of sexual abuse both for perpetrators and protection for victims of criminal acts. The term criminal law policy is generally interpreted as an effort to realize good regulations in accordance with the circumstances and situations at one time. Trying to make a better regulation in the future that applies to society and to be able to achieve what the ideals of society.